we have that Ht1 (x,y,z) - Ht2 (x,y,z) = Js and for the special case Ht1 (x,y,z) - Ht2 (x,y,z) = 0 where there is no surface current. At a boundary with Js =0, which for simplicity lets asume is at at x = a, then knowing that Ht1 and Ht2 are the magnetic fields to the left and right of the boundary respectively, we can then re write the boundary condition as lim e->0 Ht1 (a-e,y,z) - Ht2 (a+e,y,z) = 0 from which. Ht'(a,y,z) = 0 would follow if Ht1 (x,y,z) = Ht2 (x,y,z)?(adsbygoogle = window.adsbygoogle || []).push({});

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# A twist on Maxwell's equations boundary conditions

**Physics Forums | Science Articles, Homework Help, Discussion**